Playing the game: corporate social responsibility and the games industry. Issue 3 (21st March 2013) - Jones, Peter; Comfort, Daphne; Hillier, David
Abstract : This paper provides an exploratory review of both the corporate social responsibility (CSR) agendas and achievements being publicly addressed by the world's leading games companies, and offers some wider reflections on the ways these companies are constructing and pursuing CSR strategies. The paper begins with a short discussion of the origins and characteristics of CSR and a thumbnail sketch of games and the games industry. The empirical material for the paper is drawn from the CSR material posted on the Internet by the world's top 10 games companies. The findings reveal that although the majority of the top 10 games companies provide some information on their approach to CSR, only a minority claim to be integrating CSR into their core business activities. Although the companies emphasize their commitment to promoting responsible gaming, they offer little if any commentary on what many critics see as the potentially damaging human consequences of the irresponsible development and playing of games. The majority of the top 10 games companies also address a wide range of impacts within the marketplace, the workplace, the environment and communities in which they operate. Although the leading games companies generally adopt a positive stance towards CSR, the independent external assessment of the reporting process is limited. More generally, the paper offers some critical reflections on the CSR agenda currently being pursued by the games industry. The paper provides an overview and some reflections on the CSR agenda being pursued by some of the world's leading games companies, and as such, it will interest academics in business and management, and information systems and media departments, a range of people working in management positions within the games industry and those professionals who work with the industry. Copyright © 2013 John Wiley & Sons, Ltd.